Smad-Dependent Recruitment of a Histone Deacetylase/Sin3A Complex Modulates the Bone Morphogenetic Protein-Dependent Transcriptional Repressor Activity of Nkx3.2 - Kim, Dae-Won (American Society for Microbiology, 2003)
We have previously shown that Nkx3.2, a transcriptional repressor that is expressed in the sclerotome and developing cartilage, can activate the chondrocyte differentiation program in somitic mesoderm in a bone morphogenetic protein (BMP)-dependent manner. In this work, we elucidate how BMP signaling modulates the transcriptional repressor activity of Nkx3.2. We have found that Nkx3.2 forms a complex, in vivo, with histone deacetylase 1 (HDAC1) and Smad1 and -4 in a BMP-dependent manner. The homeodomain and NK domain of Nkx3.2 support the interaction of this transcription factor with HDAC1 and Smad1, respectively, and both of these domains are required for the transcriptional repressor activity of Nkx3.2. Furthermore, the recruitment of an HDAC/Sin3A complex to Nkx3.2 requires that Nkx3.2 interact with Smad1 and -4. Indeed, Nkx3.2 both fails to associate with the HDAC/Sin3A complex and represses target gene transcription in a cell line lacking Smad4, but it performs these functions if exogenous Smad4 is added to these cells. While prior work has indicated that BMP-dependent Smads can support transcriptional activation, our findings indicate that BMP-dependent Smads can also potentiate transcriptional repression, depending upon the identity of the Smad-interacting transcription factor.